Polarizing moral panics: a theory and its application to the refugee crisis in Poland - Zielińska, Iwona (Deviant behavior, 2022)
The aim of this paper is to propose a corrective of moral panic theory by introducing a concept of polarizing moral panics. We believe that the significant social and technological changes that have occurred since the 1970s have made the classical concept of moral panic less useful to describe and analyze most of the contemporary cases because it fails to include a variety of voices and a more divisive nature of modern moral panics. Polarizing moral panics are recurrent eruptions in an ongoing process of transformation of normative systems that manifest themselves in the intensive, media-amplified polarization of society over an issue, a condition or a group of persons. This leads to a clash between two moral communities and their respective and competitive visions of social order: one more conservative, the other more liberal. This can be fueled by employing politics of fear by politicians and other interest groups for political benefits. The first part of the article discusses the theory and the application of polarizing moral panics. The second part focuses on the refugee crisis in Poland in 2015-2016 as an illustration of the concept and its use to gain votes in a parliamentary election.